2020
DOI: 10.1186/s13052-020-0815-7
|View full text |Cite
|
Sign up to set email alerts
|

Risk factors and treatments for disseminated intravascular coagulation in neonates

Abstract: Background Although disseminated intravascular coagulation (DIC) is a critical disease, there is few gold standard interventions in neonatal medicine. The aim of this study is to reveal factors affecting neonatal DIC at birth and to assess the effectiveness of rTM and FFP for DIC in neonates at birth. Methods We retrospectively evaluated DIC score on the first day of life in neonates with underlying conditions associated with DIC. DIC in neonates w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 21 publications
(19 citation statements)
references
References 29 publications
0
19
0
Order By: Relevance
“…Furthermore, DIC scores before treatment in Group 2 were higher than in Group 1 (4.7 vs 3.6, P < 0.05). Hence, they concluded that rTM and FFP were effective therapies for neonatal DIC [44].…”
Section: Combination Therapymentioning
confidence: 99%
“…Furthermore, DIC scores before treatment in Group 2 were higher than in Group 1 (4.7 vs 3.6, P < 0.05). Hence, they concluded that rTM and FFP were effective therapies for neonatal DIC [44].…”
Section: Combination Therapymentioning
confidence: 99%
“…A small randomized trial by Gross et al previously showed that treatment with FFP yielded no difference in the outcome of DIC [18]. However, a recent study by Go et al showed that FFP in combination with recombinant human soluble thrombomodulin could be beneficial for the treatment of neonatal DIC [33].…”
Section: Discussionmentioning
confidence: 99%
“…The most crucial diagnostic tests to make a correct neonatal DIC diagnosis are the platelet count, D-dimer or FDP, PT, PTT, and fibrinogen [ 13 ]. The DIC diagnostic criteria of the Japan Society of Obstetrical, Gynecological & Neonatal Hematology, JSOGN, covers PLT, PT-INR, fibrinogen and d-dimer [ 14 ]. Neonates are given a score based on these factors ranging from 0 to 8.…”
Section: Reviewmentioning
confidence: 99%